Preparation of orodispersible films using semisolid extrusion 3D printing: A versatile manufacturing approach - Turković, Erna; Vasiljević, Ivana; Parojčić, Jelena (Archives of Pharmacy, 2025)
Orodispersible films (ODFs) emerged as a patient-friendly dosage form that is particularly suitable for pediatric therapy, where swallowing difficulties often interfere with adherence to therapy. In this study, the preparation of ODFs using semi-solid extrusion (SSE) 3D printing was investigated as an alternative to the conventional solvent casting method. Four hydrophilic polymers – hydroxypropyl cellulose (HPC), polyethylene glycol-polyvinyl alcohol graft copolymer (PVA-PEG), maltodextrin (MDX) and sodium alginate (SA) – were used either individually or in binary blends, with caffeine selected as the model active ingredient. Films were printed on an Ultimaker 2+ system and evaluated for uniformity, thickness, porosity, moisture content, mechanical strength, disintegration and drug release. Formulations containing only MDX or PVA-PEG exhibited poor printability due to leakage and spreading, while other systems showed reproducible film deposition and satisfactory dimensional stability. Binary blends generally resulted in increased film thickness. SA-based films showed the lowest porosity and moisture absorption, while HPC films exhibited favorable mechanical properties. The investigated samples achieved rapid disintegration and complete release of the caffeine. These results confirm the potential of SSE 3D printing as a versatile manufacturing platform for customizable ODFs that enable precise dosing and patient-centric design for pediatric drugs.